Electrode Materials And Electrolytes For Aluminum-Ion Accumulators - Benešová, Petra (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
This article presents the topic of aluminum-ion batteries, which may become an available alternative to commercially used lithium-ion batteries. Theoretical part of the paper focuses on the basic principles of aluminum-ion accumulators, their advantages in comparison with lithium-ion batteries, and the current state of research on electrode materials and electrolytes for Al-ion batteries. The experimental part deals with preparation of carbon based cathode material, ionic liquid electrolyte and subsequent assembly of the electrode cell. Basic measurements were made to verify the electrochemical activity of the assembled cell. Eventually, the obtained results and following procedures or process modifications are discussed.
Keywords: aluminum-ion; cathode material; electrolyte; ionic liquid